ANALISIS TINGKAT KERAWANAN DAN MITIGASI BANJIR PERKOTAAN DI KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU - Irwan Azhar; Widy Afyat (INFO-TEKNIK, 2021)
Several efforts are needed in dealing with urban flood disasters to minimize the potential for large losses for the community. By mapping and knowing the pattern of flood distribution, this study was also built to determine the urban flood disaster mitigation system in Pulau Laut Utara District, Kotabaru Regency. The value of the flood susceptibility class interval aims to distinguish the flood susceptibility class, and by determining the intensity of inundation based on the inundation area and the elevation of the flood level. With processing the value from the investigation in Nort Pulau Laut covering several villages and roads, the level of vulnerability to flooding in Dirgahayu Village is 10.24% (low water level), 6.54% (medium water level), 1.33% (high water level). In Sungai Paring Village it was 2.81% (low water level), 10.18% (medium water level), 8.48% (high water level). In Baharu Village, it was 3.69% (low flood), 3.21% (medium water level), 10.87% (high water level). In Semayap Village it was 4.11% (low water level), 2.21% (medium water level), 2.58% (high water level). And in Sebelimbingan Village it was 4.67% (low water level), 3.90% (medium water level), and 8.25% (high water level). With intervals from each flood location, a value of 73.98 was obtained in the category of sufficiently prone to flooding.